2020
DOI: 10.3847/1538-4357/ab6326
|View full text |Cite
|
Sign up to set email alerts
|

On the Production of Polyols and Hydroxycarboxylic Acids in Interstellar Analogous Ices of Methanol

Abstract: This laboratory work studied the production of complex organic molecules (COMs) in pure methanol (CH3OH) ices exposed to ionizing radiation in the form of energetic electrons. The chemical evolution of the ices during the electron irradiation at 10 K and subsequent warm-up phase to 300 K was monitored online and in situ via Fourier Transform Infrared (FTIR) spectrometry. Polyols and hydroxycarboxylic acids related absorptions were observed in the infrared spectra of the irradiated ices and residues at room tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 70 publications
(76 reference statements)
2
29
0
Order By: Relevance
“…Formation of hydroxycarboxylic acids has been confirmed in several experiments simulating the production of organic species under astrophysical conditions, i.e. interstellar/cometary ice analogues at temperatures < 80K exposed to UV photons/energetic particles 12,53,54 . Interestingly, Tachibana et al 55 showed that UV-irradiated interstellar ice analogues composed of water, methanol and ammonia, as well as of pure water show liquid-like behavior over 65-150 and 50-140 K temperature ranges, respectively, which may enhance the formation of complex organic species.…”
Section: Introductionmentioning
confidence: 79%
“…Formation of hydroxycarboxylic acids has been confirmed in several experiments simulating the production of organic species under astrophysical conditions, i.e. interstellar/cometary ice analogues at temperatures < 80K exposed to UV photons/energetic particles 12,53,54 . Interestingly, Tachibana et al 55 showed that UV-irradiated interstellar ice analogues composed of water, methanol and ammonia, as well as of pure water show liquid-like behavior over 65-150 and 50-140 K temperature ranges, respectively, which may enhance the formation of complex organic species.…”
Section: Introductionmentioning
confidence: 79%
“…They were also detected in our Solar System, in the 67P comet (Goesmann et al 2015;Meringer et al 2018). It is thought that GA and EG are perfect precursors for the formation of glyceraldehyde (GCA) -the first sugar -and its saturated polyol derivative, glycerol (GCO) (Zhu et al 2020;Kaiser et al 2015;Fedoseev et al 2017). Although they have not yet been observed in the ISM, clues of their presence have been found in meteorites.…”
mentioning
confidence: 80%
“…They have been unambiguously identified in a large variety of objects and environments: in dark clouds and pre-stellar cores (Marcelino et al 2007;Öberg et al 2010;Bacmann et al 2012;Cernicharo et al 2012;Vastel et al 2014;Jiménez-Serra et al 2016), in photon-dominated regions (Guzmán et al 2014), in hot cores and giant molecular clouds (Hollis et al 2000;Martín-Pintado et al 2001;Requena-Torres et al 2008;Belloche et al 2013), in low and high mass protostar environments (Blake et al 1987;Caselli & Ceccarelli 2012;Neill et al 2014;Tercero et al 2015;Coutens et al 2015;Taquet et al 2015;Jørgensen et al 2016;Rivilla et al 2016), as well as in molecular outflows (Arce et al 2008;Codella Figure 1. GCA and GCO formation pathways adapted from (Fedoseev et al 2017) (formation of GCA and GCO from GA hydrogenation) and (Kaiser et al 2015) and (Zhu et al 2020) (formation of GCO from EG and energetic electrons).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations